2017
DOI: 10.18203/2320-1770.ijrcog20171971
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intersystem agreement between standard pelvic organ prolapse quantification system and simplified pelvic organ prolapse scoring system

Abstract: Background: Pelvic organ prolapse (POP) is one of the most common gynaecological problem encountered worldwide. The POPQ has become the most commonly used prolapse staging system since its introduction (1996). In spite of having merits to it, POP-Q has not acquired a widespread acceptance. International Urogynaecological Association (IUGA) Standardization of Terminology Committee has devised a simplified version S-POP classification system based on the ordinal stages of the POPQ. The objectives of present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Parekh et al (24) showed a near perfect inter-rater agreement of the simplified POP system for overall stages and all points within the system. Also, Singh et al (25) confirmed a substantial and near perfect agreement between POP-Q and S-POP.…”
Section: Discussionmentioning
confidence: 86%
“…Parekh et al (24) showed a near perfect inter-rater agreement of the simplified POP system for overall stages and all points within the system. Also, Singh et al (25) confirmed a substantial and near perfect agreement between POP-Q and S-POP.…”
Section: Discussionmentioning
confidence: 86%